Epithelial Cell-Associated Galectin-3 Activates Human Dendritic Cell Subtypes for Pro-Inflammatory Cytokines - Schroeder, John T.; Adeosun, Abiodun A.; Bieneman, Anja P. (Frontiers in Immunology, 2020)
There is mounting evidence that galectin-3 is a prognostic and diagnostic biomarker associated with diverse diseases and conditions, including cancer, cardiovascular disease, autoimmunity, wound healing, allergic disease, and chronic inflammation in general. Yet, whether and exactly how galectin-3 may participate in the pathogenesis of these diseases remains poorly understood. Recently, we have linked the expression of galectin-3 on the A549 epithelial cell line –an adenocarcinoma, to the activation of human basophils for the release of histamine and secretion of IL-4 and IL-13. These responses proved dependent on cell-to-cell contact, basophil expression of IgE, were inhibited by n-acetyllactosamine, and were ablated when basophils were co-cultured with A549 clones lacking galectin-3 expression. While recombinant galectin-3 failed to activate basophils when in solution, microspheres expressing this lectin did so by mimicking the responses seen when using A549 cells. Given the IgE dependency of the basophil responses, and the fact that galectin-3 is long known to bind this immunoglobulin, we hypothesize that a similar mode of activation extends to other IgE-bearing cells. To investigate this possibility, we tested epithelial cell-associated galectin-3 for its capacity to activate human dendritic cells, including the plasmacytoid and myeloid subtypes as well as monocytes, all of which bind IgE. Indeed, results indicate that epithelial cell-associated galectin-3 activated these cellsfor robust production of TNF-α and IL-6 and up-regulated the expression of activation markers found on dendritic cells. Moreover, many of the same parameters previously observed for basophils applied to the findings herein, including evidence that matrix-bound galectin-3 (whether on epithelial cells or microspheres) facilitates this mode of activation. In contrast, IgE expression was dispensable for these galectin-3-dependent cytokine responses, implying that this lectin activates dendritic cells (and monocytes) by binding to a glycoprotein other than this immunoglobulin. Overall, these findings further demonstrate how galectin-3 mediates immune cell activation, providing novel insight into how this lectin may promote chronic inflammation underlying the pathogenesis of many diseases.